2019
DOI: 10.1172/jci.insight.130195
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CAR-T19 and autologous stem cell transplantation for refractory/relapsed non-Hodgkin’s lymphoma

Abstract: Role of funding source: UniCar Therapy provided financial support for this clinical trial, including product manufacturing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
0
16
0
2
Order By: Relevance
“…Whether CAR-T therapy has a role ahead of autoHCT remains an important clinical question. So far, a single-institution, nonrandomized, prospective study in patients with R/R NHL with an investigational CD19 CAR-T product has shown higher CR rates and superior overall survival, especially in patients with international prognostic index 3, with CD19 CAR-T compared with autologous stem cell transplant [93]. Ongoing randomized controlled trials are actively accruing for comparing CAR-T therapy (ie, axicabtagene ciloleucel [ZUMA-7, NCT03391466], tisagenlecleucel [BELINDA,NCT03570892], and lisocabtagene maraleucel [TRANSFORM, NCT03575351]) versus autoHCT in first R/R setting.…”
Section: What Are the New Advances For Car-t In Lymphoma?mentioning
confidence: 99%
“…Whether CAR-T therapy has a role ahead of autoHCT remains an important clinical question. So far, a single-institution, nonrandomized, prospective study in patients with R/R NHL with an investigational CD19 CAR-T product has shown higher CR rates and superior overall survival, especially in patients with international prognostic index 3, with CD19 CAR-T compared with autologous stem cell transplant [93]. Ongoing randomized controlled trials are actively accruing for comparing CAR-T therapy (ie, axicabtagene ciloleucel [ZUMA-7, NCT03391466], tisagenlecleucel [BELINDA,NCT03570892], and lisocabtagene maraleucel [TRANSFORM, NCT03575351]) versus autoHCT in first R/R setting.…”
Section: What Are the New Advances For Car-t In Lymphoma?mentioning
confidence: 99%
“… 112 152 There is ongoing debate in the field of lymphoma treatment as to the potential for CAR T cell therapy to be used in conjunction with, or to replace, traditional autoSCT. 153 154 …”
Section: Integration Of Hematopoietic Stem Cell Transplant and Immunomentioning
confidence: 99%
“…CD3 + T cells were cultured and activated in vitro using anti-CD3/CD28 monoclonal antibodies (Miltenyi Biotec) in a 5% CO 2 atmosphere at 37°C for 18-24 h. The activated T cells were then transduced with lentivirus (CD19-CAR, BCMA-CAR and tandem CAR) for 48 h. We also tansduced the BCMA CAR (D1) followed by CD19-CAR (D2) to obtain the T cells expressed two scFv by transduced two lentivirus. After transduction, the CAR T cells were cultured and expanded in a 5% CO 2 atmosphere at 37°C for 14 days in AIM-V medium (Gibco, Grand Island, NY, USA), supplemented with 100 IU/mL recombinant human interleukin-2 (IL-2; Peprotech, Rocky Hill, NJ, USA), 5 ng/ml recombinant human IL-7 (Peprotech), 5 ng/mL recombinant human IL-15 (Peprotech) and 10% autologous plasma [19].…”
Section: Preparation Of Car T Cellsmentioning
confidence: 99%